2013
DOI: 10.1007/s00204-013-1023-7
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cytochrome P450 1 (Cyp1) by vanadium in hepatic tissue and isolated hepatocyte of C57BL/6 mice

Abstract: The objective of the current study was to investigate the effect of vanadium (V(5+)) on Cyp1 expression and activity in C57BL/6 mice liver and isolated hepatocytes. For this purpose, C57BL6 mice were injected intraperitoneally with V(5+) (5 mg/kg) in the absence and presence of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) (15 μg/kg) for 6 and 24 h. Furthermore, isolated hepatocytes from C57BL6 mice were treated with V(5+) (5, 10, and 20 μM) in the absence and presence of TCDD (1 nM) for 3, 6, 12, and 24 h. In vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Therefore, we chose 24 h as an appropriate time point to measure the changes in protein expression. [ 25,27,40–43 ] The findings of the current study are the first to examine the effect of coexposure to MeHg and TCDD on the AHR‐regulated CYP1A enzymes in C57Bl/6 J mice liver. The effect of Hg 2+ and MeHg was clearly significant in inhibiting the mRNA expressions of liver Cyp1a1 and 1a2 induced by TCDD, and that was more pronounced at 6 and 24 h with Hg 2+ and MeHg, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, we chose 24 h as an appropriate time point to measure the changes in protein expression. [ 25,27,40–43 ] The findings of the current study are the first to examine the effect of coexposure to MeHg and TCDD on the AHR‐regulated CYP1A enzymes in C57Bl/6 J mice liver. The effect of Hg 2+ and MeHg was clearly significant in inhibiting the mRNA expressions of liver Cyp1a1 and 1a2 induced by TCDD, and that was more pronounced at 6 and 24 h with Hg 2+ and MeHg, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, we chose 24 h as an appropriate time point to measure the changes in protein expression. [25,27,[40][41][42][43] The findings Clarkson demonstrated that MeHg undergoes biotransformation resulting in the release of Hg 2+ in rats using isotope exchange for specific determination and other analytical methods. [44] In addition, oxidative stress induced by MeHg leads to the release of superoxide anion that is involved in the biotransformation mechanism as it cleaves the C-Hg bond to form Hg 2+ in rat liver slices.…”
Section: Discussionmentioning
confidence: 99%
“…A second field addressing the stress responses of cells exposed to chemicals is the upregulation of detoxifying or downregulation of activating metabolism (Godoy et al 2013;El-Sherbeni and El-Kadi 2014;Abdelhamid et al 2013;Grinberg et al 2014). Metabolism still represents one of the major challenges for in vitro system development (Hammad 2013;Reif 2014;Godoy 2010Godoy , 2011.…”
mentioning
confidence: 99%
“…• Based on in vitro metabolizing systems, the mechanisms of the human hepatotoxic drug fenclozic acid were studied (Rodrigues et al 2013) • Three-and two-dimensional culture systems were compared with acetaminophen-induced hepatotoxicity (Schyschka et al 2013) • The study of CYP induction in isolated mouse hepatocytes by vanadium (Abdelhamid et al 2013) • The key role of CTNNB1 in acetaminophen toxicity in mouse liver hepatoma cells (Singh et al 2013) • The study of combined effects of carcinogens in mouse liver (Kuroda et al 2013) • The study of toxicokinetics of acrylamide in primary rat hepatocytes (Watzek et al 2013) • The study of glucose homeostasis in rat liver (Zhang et al 2013) We hope that this special issue will provide readers with a clearer understanding of the complex field of hepatotoxicity.…”
mentioning
confidence: 99%